Home advantage in football: Examining the effect of scoring first on match outcome in the five major European leagues - Lago-Penas, C.; Gomez-Ruano, M.; Megias-Navarro, D.; Pollard, R. (International Journal of Performance Analysis in Sport, 2016)
The aim of the current study was to examine the importance of scoring the first goal on the match outcome in football and to determine if this influence depends on the minute in which the first goal is scored. The sample consisted in all the matches played in the season 2014/2015 in the English FA Premier League (n=380), French Ligue 1 (n=380), Spanish La Liga (n=380), Italian Serie A (n=380) and German Bundesliga (n=306). Data were examined using classification tree analysis and a linear regression analysis. The results showed that home teams scored first in 57.8 % of matches and went on the obtain 84.85% of points won in these games. In contrast when the away team scored first, they obtained only 76.25% of subsequent points. These differences were further influenced by the quality of the teams and by the match period in which the first goal was scored.